The Gap Between Prevalence and Awareness in Autoimmune Thyroid Diseases: A Systematic Synthesis and MetaAnalysis (Eurasian Medical Research Periodical, 2026)
Autoimmune thyroid diseases (AITD), primarily comprising Hashimoto’s thyroiditis (HT) and Graves’ disease (GD), represent the most prevalent group of autoimmune disorders globally, affecting approximately 5% of the general population (Hu et al., 2022). The pathogenesis of AITD involves a complex interplay between genetic susceptibility, environmental triggers, and immune dysregulation, leading to the production of thyroidspecific autoantibodies such as anti-thyroid peroxidase (TPOAb) and anti-thyroglobulin (TgAb). Over the last decade, epidemiological shifts have been observed, with a steady increase in the incidence of AITD in both iodine-sufficient and formerly iodine-deficient regions. While the implementation of Universal Salt Iodization (USI) programs has been a cornerstone of global public health, reducing the prevalence of endemic goiter, it has paradoxically been associated with a rise in thyroid autoimmunity (Botello et al., 2020). This phenomenon necessitates a transition in public health focus: from basic iodine deficiency to the more nuanced management of chronic autoimmune inflammation.